Synthesis of novel 3-(2-bromophenyl)-4-substituted-1H-1,2,4-triazole- 5(4H)-thiones derivatives - Safonov, A. A.; Nevmyvaka, A. V.; Сафонов, Андрій Андрійович; Невмивака, Аліна Валентинівна; Сафонов, А. А.; Невмывака, А. В. (Запорізький державний медичний університет, 2020)
A wide range of biological activity of 1,2,4-triazole derivatives (anti-inflammatory, antiviral, antitumor, immunostimulating, etc.) and the availability of sources for their preparation determine the prospects of using compounds of this class to create modified derivatives based on them and, as a result, medicines. Derivatives of 1,2,4-triazole have already established themselves both in the agricultural sector and in veterinary medicine and pharmacy. The aim of work was to synthesize 3-(2-bromophenyl)-4-substituted-1H-1,2,4-triazole-5(4H)-thiones, 2-((5-(2-bromophenyl)-4-methyl- 4H-1,2,4-triazole-3-yl)thio)acetic acids and their salts. Materials and methods. 3-(2-Bromophenyl)-4-substituted-1H-1,2,4-triazole-5(4H)-thiones (4a-4c) were synthesized by refluxing 1 mol 2-(2-bromobenzoyl)-N-substitutedhydrazinecarbothioamides (3a-3c) with 2 mol KOH in water medium and after cooling neutralized with acetic acid. 2-((5-(2-Bromophenyl)-4-substituted-4H-1,2,4-triazole-3-yl)thio)acetic acids (5a-5c) were obtained by refluxing the solution of 0,1 mol NaOH and substances 4a-4c respectively. It was dissolved in 2-propanol medium with 0,1 mol 2-chloroacetic acid. 2-((5-(2-Bromophenyl)-4-substituted-4H-1,2,4-triazole-3-yl)thio)acetic acid salts (6a-6o) were synthesized by adding organic amines or inorganic salts to substances 5a-5c respectively in 2-propanol or water medium. The elemental analysis of synthesized compounds was established by the universal analyzer Elementar Vario L cube (CHNS). The 1H spectra (at 400 MHz and 100 MHz) were recorded in DMSO-d6 on a Varian MR-400 spectrometer and analyzed with the ADVASP™ Analyzer program. The completeness of the reactions and the individuality of the resulting compounds were controlled by the gas chromatograph Agilent 7890B with a 5977B mass spectrometry detector. Results. It was synthesized new 3-(2-bromophenyl)-4-substituted-1H-1,2,4-triazole-5(4H)-thionesand there derivatives, the structure of compounds was confirmed using Elemental analysis (CHNS), 1HNMR and Chromatographic mass spectral analysis. Conclusions. As a result, 21 novel compounds of 3-(2-bromophenyl)-4-substituted-1H-1,2,4-triazole-5(4H)-thiones were synthesized and characterized.

Широкий спектр биологической активности производных 1,2,4-триазола (противовоспалительная, противовирусная, противоопухолевая, иммуностимулирующая и т. д.) и доступность источников их получения определяют перспективность использования соединений этого класса для создания на их основе модифицированных производных и, как следствие, лекарственных препаратов. Производные 1,2,4-триазола зарекомендовали себя в аграрном секторе, ветеринарии и фармации. Цель работы – синтез 3-(2-бромфенил)-4-замещенных-1H-1,2,4-триазол-5(4H)-тионов, 2-((5-(2-бромфенил)-4-метил-4H-1,2,4- триазол-3-ил)тио)ацетатных кислот и их солей. Материалы и методы. 3-(2-Бромофенил)-4-замещенные-1Н-1,2,4-триазол-5(4Н)-тионы (4а–4с) синтезировали при кипячении с обратным холодильником 1 моль 2-(2-бромбензоил)-N-замещенных гидразинкарботиоамидов (3a–3c) с 2 моль КОН в водной среде и после охлаждения нейтрализовали уксусной кислотой. 2-((5-(2-Бромофенил)-4-замещенные-4H-1,2,4-триазол-3-ил)тио) уксусные кислоты (5a–5c) получены при кипении раствора 0,1 моль NaOH и веществ 4а–4с и 0,1 моль 2-хлоруксусной кислоты в среде 2-пропанола. Соли 2-((5-(2-бромофенил)-4-замещенных-4Н-1,2,4-триазол-3-ил)тио)уксусной кислоты (6a–6o) синтезировали путем добавления органических аминов или неорганических солей к веществу 5a–5c соответственно в 2-пропаноле или водной среде. Элементный анализ синтезированных соединений установили с помощью универсального анализатора Elementar Vario L cube (CHNS). 1HNMR спектры записывали в DMSO-d6 на спектрометре Varian MR-400 (на 400 МГц и 100 МГц) и анализировали с помощью программы ADVASP ™ Analyzer. Полноту реакций и индивидуальность получаемых соединений контролировали с помощью газового хроматографа Agilent 7890B с детектором масс-спектрометрии 5977В. Результаты. Синтезированы новые производные 3-(2-бромфенил)-4-замещенных-1H-1,2,4-триазол-5(4H)-тионов, структура которых подтверждена с помощью элементного анализа (CHNS), 1HNMR и хроматографического масс-спектрального анализа. Выводы. В результате синтезировано и охарактеризовано 21 соединение производных 3-(2-бромофенил)-4-замещенных-1Н-1,2,4-триазол-5(4Н)-тионов.

Широкий спектр біологічної активності похідних 1,2,4-тріазолу (протизапальна, противірусна, протипухлинна, імуностимулювальна тощо) і доступність джерел їх отримання визначають перспективність використання сполук цього класу для створення на їхній основі модифікованих похідних, а отже і лікарських препаратів. Похідні 1,2,4-тріазолу зарекомендували себе в аграрному секторі, ветеринарії та фармації. Мета роботи – синтез 3-(2-бромфеніл)-4-заміщених-1H-1,2,4-тріазол-5(4H)-тіонів, 2-((5-(2-бромфеніл)-4-метил-4H-1,2,4-тріазол- 3-іл)тіо)оцтових кислот і їхніх солей. Матеріали та методи. 3-(2-Бромофеніл)-4-заміщені-1Н-1,2,4-тріазол-5(4Н)-тіони (4а–4с) синтезували під час кип’ятіння зі зворотним холодильником 1 моль 2-(2-бромбензоїл)-N-заміщених гідразинкарботіоамідів (3a–3c) з 2 моль КОН у водному середовищі та після охолодження нейтралізували оцтовою кислотою. 2-((5-(2-Бромофеніл)-4-заміщені-4H-1,2,4-тріазол-3-іл)тіо)оцтові кислоти (5a–5c) отримали під час кипіння розчину 0,1 моль NaOH та речовин 4а–4с і 0,1 моль 2-хлороцтової кислоти в середовищі 2-пропанолу. Солі 2-((5-(2-бромофеніл)-4-заміщені-4Н-1,2,4-тріазол-3-іл)тіо)оцтової кислоти (6a–6o) синтезували шляхом додавання органічних амінів або неорганічних солей до речовини 5a–5c відповідно у 2-пропанолі або водному середовищі. Елементний аналіз синтезованих сполук встановили за допомогою універсального аналізатора Elementar Vario L cube (CHNS). 1HNMR спектри записували в DMSO-d6 на спектрометрі Varian MR-400 (на 400 МГц та 100 МГц) та аналізували за допомогою програми ADVASP ™ Analyzer. Повноту реакцій та індивідуальність сполук контролювали газовим хроматографом Agilent 7890B із детектором мас-спектрометрії 5977В. Результати. Синтезували нові похідні 3-(2-бромфеніл)-4-заміщених-1H-1,2,4-тріазол-5(4H)-тіонів, структура яких підтверджена за допомогою елементного аналізу (CHNS), 1HNMR та хроматографічного мас-спектрального аналізу. Висновки. В результаті синтезували й cхарактеризували 21 сполуку похідних 3-(2-бромофеніл)-4-заміщених-1Н-1,2,4-триазол- 5(4Н)-тіонів.
Синтез нових похідних 3-(2-бромфеніл)-4-заміщених-1H-1,2,4-тріазол-5(4H)-тіонів
Синтез новых производных 3-(2-бромфенил)-4-замещенных-1H-1,2,4-триазол-5(4H)-тионов
Keywords: 1,2,4-triazole; thiones; acids; salts; heterocyclic compounds; 1,2,4-тріазол; тіони; кислоти; солі; гетероциклічні сполуки; 1,2,4-триазол; тионы; кислоты; соли; гетероциклические соединения